Didymium dubium - Krivomaz, Т. І.; Michaud, А.; Minter, D. W. (CABI, 2010)
Diagnostic features. Nivicolous species of Didymium can be identified provisionally in the field by the architecture and colour of the plasmodiocarps. Didymium dubium in particular has continuous white to pale gray plasmodiocarps with scattered depressions in the surface.
Keywords: myxomycetes; міксоміцети; Didymium dubium